Rethinking the Sustainable Livelihoods Framework: An Indigenous Perspective - Kamal, Asfia Gulrukh; Martens, Tabitha (Journal of Aboriginal Economic Development, 2015)
Sustainable Livelihoods Framework (SLF), a widely used analytical tool originating from development studies, aims to identify livelihoods dynamics and suggest solutions for marginalized populations. In this article we argue that a fixed asset model defined within the sustainable livelihoods framework limits adequate understanding of Indigenous culture and livelihoods and therefore fails to acknowledge the historical power imbalances. By making a critical analysis of the term "capital" used in the sustainable livelihoods framework, we argue that for an ethical understanding of development politics, the sustainable livelihoods framework should be supple and accord with a culturally appropriate analysis, definition and terms. This paper presented its argument based on O-Pipon-Na-Piwin Cree Nation's perspective on sustainable livelihoods and relationships.